Population Impact & Efficiency of Benefit‐Targeted Versus Risk‐Targeted Statin Prescribing for Primary Prevention of Cardiovascular Disease. Issue 2 (February 2017) - Pletcher, Mark J.; Pignone, Michael; Jarmul, Jamie A.; Moran, Andrew E.; Vittinghoff, Eric; Newman, Thomas
Abstract : Background: Benefit‐targeted statin prescribing may be superior to risk‐targeted statin prescribing (the current standard), but the impact and efficiency of this approach are unclear. Methods and Results: We analyzed the National Health and Nutrition Examination Survey (NHANES) using an open‐source model (the Prevention Impact and Efficiency Model) to compare targeting of statin therapy according to expected benefit (benefit‐targeted) versus baseline risk (risk‐targeted) in terms of projected population‐level impact and efficiency. Impact was defined as relative % reduction in atherosclerotic cardiovascular disease in the US population for the given strategy compared to current statin treatment patterns; and efficiency as the number needed to treat over 10 years (NNT10, average and maximum) to prevent each atherosclerotic cardiovascular disease event. Benefit‐targeted moderate‐intensity statin therapy at a treatment threshold of 2.3% expected 10‐year absolute risk reduction could produce a 5.7% impact (95% confidence interval, 4.8–6.7). This is approximately equivalent to the potential impact of risk‐targeted therapy at a treatment threshold of 5% 10‐year atherosclerotic cardiovascular disease risk (5.6% impact [4.7–6.6]). Whereas the estimated maximum NNT10 is much improved for benefit‐targeted versus risk‐targeted therapy at these equivalent‐impact thresholds (43.5 vs 180), the average NNT10 is nearly equivalent (24.2 vs 24.6). Reaching 10% impact (half the Healthy People 2020 impact objective, loosely defined) is theoretically possible with benefit‐targeted moderate‐intensity statins of persons with expected absolute risk reduction >2.3% if we expand age eligibility and account for treatment of all persons with diabetes mellitus or with low‐density lipoprotein >190 mg/dL (impact=12.4%; average NNT10 =23.0). Conclusions: Benefit‐based targeting of statin therapy provides modest gains in efficiency over risk‐based prescribing and could theoretically help attain approximately half of the Healthy People 2020 impact goal with reasonable efficiency.